TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN XYZ DI JABODETABEK - Rizki Fatiha; Agriani Hermita Sadeli; Erna Rachmawati; Lucyana Trimo (Universitas Galuh Ciamis, 2021)
Rapid technological advances allow access to information about healthy food nowadays is no longer an important issue. Sellers and buyers can interact directly through the internet without having to go out of the house. The large number of e-commerce and marketplace options makes competition between retailers even tighter. XYZ is one of the many e-commerce that sells vegetables and fruits. The intense competition amid a pandemic demands XYZ to continue making improvements in service quality and product quality. This study aims to measure the level of satisfaction and level of consumer loyalty of XYZ in Jabodetabek. This research was conducted by distributing questionnaires to XYZ consumers via Instagram’s direct message. The research used a quantitative design with an explanatory survey as the technique of the research. The number of samples used in this study was 96 samples with respondents who happened to shop for vegetables and fruits from XYZ and live in Jabodetabek. Data analysis that was used in the research was descriptive, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that XYZ consumers in Jabodetabek were very satisfied with the services provided by XYZ. They also tend to have a very high level of loyalty.